The Swimming Start: Measurement, Importance and Enhancement through Pre-Race Interventions - HELEN PARROTT (2023)
The swimming start is underpinned by horizontal velocity, which is determined by power output on the block and can be enhanced through pre-race interventions. This thesis aimed to determine the accuracy of start times measured using a single panning camera analysis system, to quantify start times to total race time and investigate pre-race interventions to enhance start and countermovement jump performance. Study one determined the accuracy and reliability of a single panning camera analysis system to measure start time and within the context of a predetermined smallest worthwhile change (≥ 0.187 s). Systematic error and 95% limits of agreement were lower than the smallest worthwhile change for all start times. Study two quantified start time as a percentage of total race time. Start time was found to contribute up to 26.07% of total race time, with males having a lower start contribution than females, and differences between nationalities also identified. Study three assessed how isometric and ballistic postactivation potentiation conditioning activities impact start and countermovement jump performance. Ballistic postactivation potentiation elicited significantly higher countermovement jump height (p = 0.045) and peak power output (p = 0.004) values compared to the control. No significant differences were found for isometric postactivation potentiation compared to the control. Study four investigated the differences between an insulated, foil lined heat garment and trousers with heat elements across the thighs and calves. No significant changes in performance were found (p > 0.050) despite significantly higher muscle temperatures following active heat maintenance. Peak power output was significantly different following passive heat maintenance compared to the control (p = 0.047). This thesis suggests that coaches with sprint athletes should seek opportunities to enhance start performance, which can contribute a large proportion of total race time. Ballistic postactivation potentiation and passive heat maintenance can significantly increase peak power output and potentially start time, although this is on an individual basis. Pre-race interventions should be trialled within training and can be accurately monitored using a single panning camera analysis system to identify significant changes.